Notioperilitus gen. nov., a new braconid genus (Hymenoptera: Braconidae: Euphorinae) from Australia, parasitoid of adult Morabinae (Orthoptera: Eumastacidae), with remarks on the generic placement of two Afrotropical euphorine species - Belokobylskij, Sergey A. (Zootaxa, 2018)
The new Euphorinae genus, Notioperilitus Belokobylskij, gen. nov., with type species Perilitus morabinarum Blackith, 1967, from Australia, a parasitoid of adult Orthoptera in the subfamily Morabinae, is described and illustrated. Its taxonomic position and biological peculiarities are discussed. Additionally, modern generic positions (in Centistoides van Achterberg 1992, and Marshiella Shaw 1985 respectively) are proposed for two Malagasy species described by Granger (1949), Centistes ophthalmicus Granger, 1949 and Microctonus madecassus Granger, 1949, which are illustrated. A lectotype of Microctonus madecassus Granger is designated.